Pengaruh Perilaku Kerja dan Gaya Kepemimpinan Partisipatif terhadap Kepuasan Kerja karyawan - Raynaldo Raynaldo; Sudharto P Hadi (Universitas Diponegoro, 2016)
Employee is a main asset who have an important role in the development and the future of thecompany. One factor that determined employee’s performance is job satisfaction. Job satisfaction atPatra Jasa Semarang Convention Hotel has been fluctuated. It can be seen from absenteeism andemployees performance evaluation.The purpose of this study is to investigate the influence of work behavior and participative leadershipstyle to job satisfaction at permanent employees Patra Jasa Semarang Convention Hotel. The type of thisresearch is explanatory with the number of respondents were 108 permanent employees. The samplingmethod using saturated sampling technique. The analytical method in this study are correlationcoefficient, determination coefficient, simple linear regression, multiple linear regression, t test, F testand classical assumption with the help of IBM SPSS program.The results of this study are positive corelation between of work behavior and participative leadershipstyle to work behavior partially and simultaneously. Based on the results of the regression analysis, it isknown that the variable behavior of labor and participative leadership style influence on job satisfactionwith a coefficient of 0.209 and 0.608. The advice given to the company is the company must considercultural approaching to motivate the employee to understand the command of leader and there is neededa teamwork and good comunication between leader and employee.